The nature of détente - Stevenson, R; Stevenson, Richard William (1983)
﻿ This study attempts to ascertain the nature of détente by clarifying the term, identifying common elements working for and against détente, and considering whether the history of various periods of détente suggests a cyclical or progressive pattern. First, détente is defined as a process - not a condition, policy or historical period. More specifically, it is the process of easing tension between states whose interests are so radically divergent that the possibilities of reconciliation are inherently limited. Second, by examining the post-war Soviet-American relationship and focusing individually on the four periods of détente that occurred during this time ('spirit of Geneva' 1955; 'spirit of Camp David' 1959; Post- Missile Crisis détente 1963-4; Moscow détente 1972-5), those common elements influencing the rise and fall of détente emerge. They include the influence of individual leaders, the fear of nuclear war, the self-perceived strength of the superpowers, the convergence of superpower special interests, the changing perceptions of détente and the national interest, and the difficulties in reaching a common code of détente. Finally, the character of détente is found to be progressive due to the legacy left by each period.